Assessment of bankruptcy and new opportunities for development of small and medium-sized businesses in Russia - T. A. Shpilkina (Путеводитель предпринимателя, 2020)
The author analyzes and assesses the bankruptcy of small and medium business in Russia in 2015-2018. Presents the self-employed in foreign countries and the Russian Federation. The main parameters and provisions ofthe law on self-employed in Russia are shown, its importance for the development of small and medium-sized enterprises in the near future is determined.